Distribution of External Load During Acquisition Training Sessions and Match Play of a Professional Soccer Team. Issue 12 (December 2021) - Castillo, Daniel; Raya-González, Javier; Weston, Matthew; Yanci, Javier
Abstract: Castillo, D, Raya-González, J, Weston, M, and Yanci, J. Distribution of external load during acquisition training sessions and match play of a professional soccer team. J Strength Cond Res 35(12): 3453–3458, 2021—The aim of this study was to use global position systems to analyze the external loads of the 3 different acquisition training sessions (ATS) with competitive matches in professional soccer players over a 6-week period. Sixteen professional soccer players participated in the study, which analyzed the distribution of external load during the training microcycle of a professional soccer team. The 3 types of ATS undertaken by the players were as follows: ATS1 (strength), ATS2 (endurance), and ATS3 (speed). The total distance covered, the distance covered at above 14 km·h −1, the distance covered >21 km·h −1, the number of high accelerations (>3 m·s −2 ), and player load were recorded. The results showed that external loads were consistently higher during matches when compared with all training sessions (range of effect sizes: 1.06–3.38). Between training session comparisons revealed higher external loads during ATS1 and ATS2, when compared with ATS3 (range of effect sizes: 0.60–2.41). The only external load variable that differed between ATS1 and ATS2 was the distance covered >21 km·h −1, which was higher for ATS1. Our findings suggest that technical staff should consider the physical demands of weekly periodization to understand the training process regarding optimizing player physical performance.